Penguatan Literasi Digital melalui Edukasi Screen Time Sehat pada Anak Usia Dini - Faisal, Aurellia Nazira; Putri, Tasya Amellia; Puteri, Revani Amanda; Adiantara, Galih (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This community service activity aims to improve preschool children's understanding of good screen use and strengthen basic digital literacy. This event was held at Al-Barkah Islamic Kindergarten and was attended by 21 kindergarten children as participants. The methodology applied included interactive presentations and light discussions, which included introduction to gadget devices, proper timing for screen use, age-appropriate content selection, as well as alternative activities that did not involve gadgets. Evaluation was carried out using pretest and posttest through observation and question and answer sessions. The results show a significant increase in understanding. The level of children's understanding of the time limit for using gadgets increased from 28% before the activity to 81% after. In addition, children's ability to distinguish content based on age also increased from 24% to 85%. Furthermore, 90% of children were able to mention at least two alternative activities that did not have gadgets. These findings show that digital literacy education at an early age succeeds in forming more appropriate and balanced gadget use habits.